A Sociolinguistic Analysis of Accent in One Piece Live Action Series: Accent, society, impact - Pongoh, Cristian; Sanerita T. Olii; Agustine C. Mamentu (Program Studi Pendidikan Bahasa Inggris, 2024)
This research aimed to identify and describe the impact of English accent in society that exist in the “One Piece” Live Action Series. Since this series really portrayed the society with many characters and many different accents. This series only analyzed one character and one accent, which is Sanji with his British accent. In making this research, the writer used qualitative method since the data are in the type of words and lines of conversations rather than numbers. There are two sources that he used, from the series and the internet. He used some steps of Miles and Huberman (1994) theory in analyzing the data. Sociolinguistic approach is applied in order to analyze the data. The data in this research were taken from the dialogues of the series, then the accent from those dialogues later be analyzed deeper in order to find the impact in society. As the result of the analysis, there was 29 dialogues from four episodes. With 6 dialogues from episode 5, 8 dialogues from episode 6, 6 dialogues from episode 7, and 9 dialogues from episode 8. With the impact of English accent in society from each dialogue per episodes. The impact of English accent in society that can be found are like flirty guy behaviors, showing kindness and helpful towards the people who needed, pay attention and supportive towards friends who needed, protective to something/someone precious, have no intention to lose and competitive towards a friend with a rivalry feeling, joking sarcastically towards friend, and others.